HYBRID MATERIAL BASED IN METAL-ORGANIC FRAMEWORK SUPPORTED ON ACTIVATED CARBON AS NOVEL MATERIALS FOR CO2 ADSORPTION FOR ENVIRONMENTAL APPLICATIONS - Sepúlveda, Erwin; Méndez-Herrera, Paola; Sepúlveda-Reyes, Margarita; Ahumada-Rudolph, Ramón; Novoa, Vanessa (Journal of the Chilean Chemical Society, 2025)
A composite of Ni-MOF-5 (NixZn4-xO(HCOO)3(BCD)3 (0<x<4)) and activated carbon were synthesized through a microwave synthesis method with reflux. Various characterization techniques were performed, including XRD, TGA, SEM, EDS, FT-IR, and BET isotherm. The surface study of the material shows the presence of crystals with a cubic structure of Ni-MOF-5 with sizes smaller than 10 µm. A superficial area of 718 m2/g and thermostability with a mass loss of 4.72% at 459°C of the metal-organic framework were observed. The results for different CO2 concentrations at 1 bar and 25 °C show that the adsorption capacity had a linear relationship between % CO2 and the amount of CO2 adsorbed by the hybrid material. The results also showed that by increasing the working temperature in the CO2 adsorption process and keeping the percentage of CO2 constant, the amount of adsorbed CO2 decreases linearly. The adsorption kinetics of CO2 on the prepared hybrid material are consistent with the intraparticle diffusion model, where diffusion is the rate-limiting step. The adsorption of CO2 is energetically and kinetically favorable due to the micro-mesoporosity of the material that allows the entry of CO2 molecules into the pores.